Does critical velocity represent the maximal lactate steady state in youth swimmers? - Machado, M. V.; Borges, J. P.; Galdino, I. S.; Cunha, L.; Sá Filho, A. S.; Soares, D. C.; Andries Junior, O. (Science & Sports, 2019)
Objectives: We investigated the relation between critical velocity (CV) and maximal lactate steady state (MLSS) in swimmers athletes of youth categories. Equipment and methods: Twenty well-trained competitive youth swimmers (13.84±0.89y) participated in the study. CV was determined by the linear regression slope b between the distance and time obtained in four maximal bouts of 50, 100, 200 and 400-meters (m) swimming freestyle each. To determine the MLSS, the subjects randomly performed three series of four bouts of 400m (3×4×400m) with velocity corresponding to 98, 100 and 102% of the CV. We collected 25µl of blood from their fingertips at rest and at the end of each bout. MLSS intensity was defined as the highest workload that could be maintained for a long period of time in which the blood lactate concentration did not increase more than 1mmol·L-1. Results: CV was significantly higher than velocity corresponding to MLSS in adolescents swimmers (1.31±0.05 vs. 1.29±0.05m·s-1, P<0.001). However, a high correlation (r=0.89, P<0.0001), as well as agreement determined by Bland-Altman plots (agreement limits of 95%) and a trivial Cohen's d effect size (d=0.16) were observed between CV and MLSS. Conclusion: Although CV overestimates MLSS in young swimmers, the strong correlation, good agreement and trivial effect size between them suggest that using CV is reliable for prescription and swimming training assessment.